Cu-Catalyzed selective C3-formylation of imidazo[1, 2-a]pyridine C–H bonds with DMSO using molecular oxygen. Issue 10 (18th December 2014) - Cao, Hua; Lei, Sai; Li, Naiying; Chen, Longbin; Liu, Jingyun; Cai, Huiyin; Qiu, Shuxian; Tan, Jingwen
Abstract : Using the widely available DMSO as the formylation reagent under oxidative conditions, an efficient Cu-catalyzed C3-formylation reaction of imidazo [1, 2- a ]pyridine C–H bonds to directly generate structurally sophisticated 3-formyl imidazo[1, 2- a ]pyridine derivatives has been developed. Abstract : Using the widely available DMSO as the formylation reagent under oxidative conditions, an efficient Cu-catalyzed C3-formylation reaction of imidazo[1, 2- a ]pyridine C–H bonds to directly generate structurally sophisticated 3-formyl imidazo[1, 2- a ]pyridine derivatives has been developed. The reaction proceeded to generate products in good yields, and used the environmentally friendly molecular oxygen as the oxidant.